Fear of crime among Chinese immigrants in Metro-Detroit - Wu, Yuning (Crime, law and social change, 2014)
Although a great deal of research has been conducted on fear of crime among the general public, much less is known about such fear among immigrants. Intensified fear may have detrimental consequences on immigrants’ lifestyles, acculturation process, and responses to law enforcement. Based on survey data collected from 148 Chinese immigrants in Metro-Detroit, this study assesses the effects of a variety of general and immigrant-specific explanatory factors on Chinese immigrants’ fear of crime. Results show that Chinese immigrants who had greater perceived risks of victimization, stronger perceptions of crime problems in home city, and lower English proficiency tended to have higher levels of fear of crime. Implications for policy and future research are discussed.